Exploring Spatial Associations between On-Sale Alcohol Availability, Neighborhood Population Characteristics, and Violent Crime in a Geographically Isolated City. (27th November 2013) - Han, Daikwon; Gorman, Dennis M.
Abstract : Objectives . Despite the increasing evidence of the associations between alcohol availability and violence, there are still inconsistent findings on the effects of on- and off-sale alcohol outlets on violent crime. The aim of this study was to examine spatial associations between on-sale alcohol availability, neighborhood characteristics, and violent crime in a geographically isolated city in Texas. Methods . Geographically weighted regression (GWR) and global regression models were employed to analyze the nature of the spatial relationship between violent crime, neighborhood sociocultural characteristics, and on-sale alcohol environment. Results . We found strong effects of neighborhood characteristics combined with on-sale alcohol availability on violence outcomes. Several neighborhood variables combined with alcohol availability explained about 63% of the variability in violence. An additional 7% was explained by the GWR model, while spatially nonstationary associations between violence and some predictor variables were observed. Conclusions . This study provided more credible evidence of the influence of on-sale alcohol outlets on violence in a unique setting. These findings have important policy implications in addressing the question of public health consequences of alcohol-related violence in local contexts.